Changes in quality of life over time through the lens of young people aged 18–24 in 2016 in Gauteng Province of South Africa - Edmore Marinda; Yashena Naidoo; Mmakotsedi Magampa; Abongile Pindo; Mercy Ngungu; Kwanele Qonono; Lwando Mdleleni; Makgalane Ramontsha (PLoS ONE, 2025)
Young people in South Africa face many challenges that include high unemployment, economic hardships, high rates of crime, alcohol and substance abuse, violence, anxiety, depression, and trauma. Quality-of-life (QoL) surveys done over time help identify the challenges faced by this group and help with designing appropriate programmes to mitigate these challenges. The study aimed to assess changes in the QoL of young people aged 18 to 24 in 2016, using a 32 to 38-year-old cohort as a comparison group. Mixed effects regression models with time and age-group interaction terms were used to assess changes in QoL between 2016 and 2024 for the two age groups using four unlinked surveys. Marginal QoL mean scores decreased from 62.5 in 2016 to 59.2 in 2024 for youth living in Gauteng province, South Africa, while for the older cohort, the mean score initially increased from 62.5 to 64.2 between 2016 and 2018 but had decreased to 60.1 by 2024. QoL scores for the older age group were marginally higher compared to the younger group in 2018 (64.2 vs 63.5), 2021 (61.6 vs 60.9), and 2024 (60.1 vs 59.2). Among youth, the following QoL domains contributed to the observed decrease in overall QoL scores: satisfaction with government, life satisfaction, health status, and satisfaction with public services, with the only noticeable consistent increase observed in the participation domain. There were noticeable increases in the marginal mean scores for the socio-economic status domain for the older cohort after the COVID-19 epidemic, with the opposite observed among the young age group. Young people in the Gauteng province of South Africa are generally discontented and dissatisfied with life as they age. Challenges with unemployment, safety, violence, and mental health need to be urgently addressed to avoid possible unrest, as observed before and elsewhere in the country.